Electrocoalescence of water drop trains in oil under constant and pulsatile electric fields - Vivacqua, V.; Mhatre, S.; Ghadiri, M.; Abdullah, A.M.; Hassanpour, A.; Al-Marri, M.J.; Azzopardi, Barry J.; Hewakandamby, Buddhika N.; Kermani, B. (Elsevier, 2015)
This study addresses the effectiveness of constant and pulsed DC fields in promoting coalescence of dispersed water drops in an oil-continuous phase. For this purpose, a train of drops of relatively uniform size is injected into a stream of flowing sunflower oil. This stream is then admitted to a coalescing section, where an electric field is applied between a pair of ladder-shape bare electrodes. The capability of this device to enhance coalescence of droplets in a chain is investigated at different field intensities, frequencies and waveforms. The effect of the initial inter-droplet separation distance on the process performance is also addressed under constant DC fields. The dominant coalescence mechanism is found to be due to dipole–dipole interaction at low field strength, whereas electrophoresis becomes predominant at higher field strength. Experiments reveal the existence of an optimal frequency, where the average droplet size enlargement is maximized, especially at low field strengths. The droplet size at the outlet of the coalescer is also found to be dependent on the field waveform.